Chemical analysis and angiotensin I-converting enzyme inhibitory activity of enzymatic hydrolysates derived from meat of goat-kids with supplemental selenium - Pérez-Ramirez,Silvia C.; Cruz-Monterrosa,Rosy; Diaz-Ramirez,Mayra; León-Espinosa,Erika B.; Aguilar-Toalá,José E.; Rosas-Espejel,Monzerrat; Ramirez-Bribiesca,J. Efren (PeerJ, 2025)
Background The effects of selenium (Se) on animal health due to its antioxidant and immune system regulatory properties are very well-documented. However, there is still a lack of scientific evidence about the effect of Se on muscle tissue. Se supplementation in ruminants will enhance the antioxidant activity of myocytes and increase angiotensin-converting enzyme (ACE) inhibitory activity. Generating bioactive peptides derived from meat could prevent the production of angiotensin II, a key player in the development of cardiovascular diseases. Methods Forty-five suckling goat kids were randomized into one of three groups: (1) CG: group without Se supplemented in the diet; (2) GSS: group with a single injectable dose subcutaneously of sodium selenite (Na2SeO3) at a dose of 0.25 mg/kg of body weight; (3) GSM: group with an oral administration of selenomethionine (SeMe) at a dose of 0.3 mg/kg of body weight). The effect of both sources of Se was evaluated on the proximate composition of meat and liver and the angiotensin I-converting enzyme inhibitory activity of meat-derived enzymatic hydrolysates. Results The kids-goat meat from the GSM group had a higher protein content (p < 0.05). The fat content gradually increased over time in the treatment GSM, which increased ca. two-fold (from 1.77 to 3.68). The degree of hydrolysis of the meat samples decreased (p < 0.05) in the treatments supplemented with Se (GSS and GSM). The degree of hydrolysis increased significantly (p < 0.05) over time in treatments with Se (GSS and GSM). The electrophoretic patterns of the enzymatic hydrolysates at two h showed a molecular weight between 23.44 and 27.5 kDa, the bands with more intensity. At 21 d of slaughter, a major degree of hydrolysis was observed in the treatments supplemented with Se (GSS and GSM) compared to the CG. Meat protein content and rate of ACE inhibition after hydrolysis improved (50% and 2%, p < 0.05) with GSM at 7 d of slaughter. After hydrolysis, the IC50 of the selenium-supplemented groups decreased (p < 0.05) the amount of CAE and IC50 values. Conclusion This is the first report describing the ACE inhibitory activity of bioactive peptides derived from goat-kids meat with supplemental. These results indicate the presence of ACE in goat meat; however, the percentage of ACE inhibition after hydrolysis was only improved with selenomethionine dosing at 7 days of slaughter. The study’s novelty indicates that supplemented selenium synergized with ACE in goat meat. It is necessary to continue these studies to identify specific bioactive peptides, antioxidant activities, and goat meat’s biological and functional value, considering it a functional food that can prevent metabolic diseases and be a healthy alternative for the human population.
Keywords: Enzyme; Peptides; Goat kids; Selenium